A Case with Recurrent Facial Palsy: Melkersson-Rosenthal Syndrome - Derya Fatma Bulut; Gulen Gul Mert; Faruk incecik; Ozlem Mihriban Herguner; sakir Altunbasak (Çukurova Üniversitesi Tıp Fakültesi Dergisi, 2014)
Melkersson-Rosenthal syndrome (MRS) is a rare neuromucocutaneous syndrome characterized by recurrent facial paralysis, orofacial edema and fissured tongue. Oligosymptomatic and monosymptomatic forms are more common than the triad. The presence of two manifestations or one manifestation with granulomatous cheilitis in biopsy is sufficient to make diagnosis of Melkersson-Rosenthal syndrome. We present a 12 years-old male who is diagnosed Melkersson-Rosenthal syndrome. [Cukurova Med J 2014; 39(4.000): 918-921]